Application of Carbon and Nitrogen Ratio in The Sangkuriang Catfish Culture Clarias gariepinus var in Tarpaulin Tanks. Issue 1 (1st April 2022) - Aziz, R; Oktaviana, A
Abstract: Sangkuriang catfish (Clarias gariepinus var) is a freshwater commodity fish that has the potential to be developed. Sangkuriang catfish farming activities still often experience problems in their implementation, especially water quality problems in the form of a buildup of organic matter that does not decompose and causes poison to catfish. The determining factor of success in growing heterotrophic bacteria in aquaculture waters is the ratio of C/N in the tank of sangkuring catfish. This study aims to determine the C/N ratio, growth rate, and survival of catfish. The results showed that the addition of a C/N ratio of 10:1 has an effect on the growth, survival rate of catfish and can reduce the ammonia content in catfish culture media.